Group 3 Late Embryogenesis Abundant Proteins in Desiccation-Tolerant Seedlings of Wheat (Triticum aestivum L.). - Ried, J. L. (1993)
Dormant seeds and young seedlings of wheat (Triticum aestivum L.) tolerate desiccation. A transcript expressed in this desiccation-tolerant tissue has been cloned and sequenced (J. Curry, C.F. Morris, M.K. Walker-Simmons [1991] Plant Mol Biol 16: 1073-1076). This wheat cDNA clone encodes a protein that is homologous to other group 3 late embryogenesis abundant (LEA) proteins. In this report, we describe the production of polyclonal antibodies to the protein product of the cDNA clone and assess group 3 LEA protein levels in desiccation-tolerant tissue. The group 3 LEA antibodies detected four major proteins in wheat with molecular masses from 27 to 30.5 kD. The genes for these proteins mapped to wheat chromosomes 1A, 1B, and 1D. The group 3 LEA proteins were present in mature seed embryos and were maintained when growth-arrested, dormant seeds were hydrated for 111 h. However, in germinating seeds the group 3 LEA proteins declined and were no longer detectable by 111 h. We severely dehydrated seedlings (more than 90% water loss) to assess group 3 LEA transcript and protein accumulation in tissues of these desiccation-tolerant plants. In response to dehydration, abscisic acid (ABA) levels increased dramatically and group 3 LEA mRNAs were induced in root, shoot, and scutellar tissue. However, group 3 LEA proteins were detected only in shoot and scutellar tissue and not in root tissue. Treatment of nonstressed seedlings with 20 [mu]M ABA resulted in low levels of group 3 LEA proteins in the roots, whereas higher levels were found in the shoot and scutellar tissue. When dehydrated seedlings were rehydrated, shoot and scutellar tissue resumed growth. The roots did not resume growth and subsequently died. New roots developed later from the scutellar tissue. Thus, in severely dehydrated wheat seedlings, the accumulation of high levels of group 3 LEA proteins is correlated with tissue dehydration tolerance.